Imagery of space in Miroslav Krleža’s short story cycle Hrvatski bog Mars (Croatian God Mars) - Brković, Ivana (Array, 2014)
The paper deals with representation of space in Miroslav Krleža’s prose cycle Hrvatski bog Mars (The Croatian God Mars), which thematises the life of Croatian soldiers (domobrani) during the First World War. Generated by various types of discourse – historical, mythological, ideological, religious, social and political – the space in Krleža’s prose cycle reveals multilayered and multiple demarcations which imply basic opposition Austrian Empire (centre) vs. Croatian space (periphery). Constituting itself as a hegemonic and colonising space of the Other, the imperial centre is the bearer of exclusively negative value connotations. On the other hand, the Croatian space of identity, determined by different temporal rhythms (historic, mythological/cyclic, utopian) in the axiological sense indicates ambivalent meanings. Connected to this, the construct of space distances itself from the traditional, cliched literary interpretations which imply oppositional evaluation of centre and periphery. Accordingly, the space in Krleža’s short story collection is determined by the historical events, i.e. political and military roles of the Habsburgs in World War One, the contemporary conditions in Croatian society, but also reveals the authors anti-war attitude. Implying the deconstruction of Austrian imperial, but also Croatian national myths, the construct of space in Hrvatski bog Mars bears imprints of Krleža’s communist inclination and revolutionary Leninist ideas as well as of the vision of the Pan-Slavic community.